KESANTUNAN BERBAHASA GURU DAN SISWA DALAM PEMBELAJARAN DARING DI SMK GONDANG - Anggita Priswantiningtyas; Hanindya Restu Aulia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2022)
Language politeness is a polite attitude in language, both written and spoken. This study deals with the politeness of the language of teachers and students in online learning at SMK Gondang during the pandemic. This study aims to describe the language politeness of teachers and students in online learning that occurs at SMK Gondang. The method used in this research is descriptive qualitative based on the object of research which is described in a description in the form of factual data source. The result of this study found that there was compliance with the principle of language politeness in the interaction of teachers and students at SMK Gondang in online learning. There are maxims of agreement, maxim of wisdom, generosity, appreciation, sympathy. In this study, it was also found that there were violation of the principle of politeness in language, namely of consensus and the maxim of wisdom. The result of the study are implied in the learning of lectures in class XI.